2019
DOI: 10.3390/molecules24173131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Complex DNA and MVs with GTF Extracted from Streptococcus mutans on the Oral Biofilm

Abstract: Streptococcus mutans is one of the principal pathogens for the development of dental caries. Oral biofilms formed by S. mutans are constructed of insoluble glucan formation induced by the principal enzymes, GTF-I and GTF-SI, in sucrose-containing conditions. However, as another means of biofilm formation, extracellular DNA (eDNA) and membrane vesicles (MVs) are also contributors. To explore the roles of eDNA and MVs for biofilm formation, short and whole size pure DNAs, two types of sub-purified DNAs and MVs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 51 publications
0
31
1
4
Order By: Relevance
“…Also prevalent in S. mutans EMVs were glucosyl hydrolases, Gtfs, and Gbps, all of which are well established S. mutans virulence attributors that play a significant role in facilitating biofilm formation (Lemos et al, 2019). GTFs were recently reported to be carried by S. mutans EMVs, and impaired biofilm formation by a gtfBC mutant was restored by exogenous addition of EMVs harvested from broth culture supernatant of the parent strain (Senpuku et al, 2019). Addition of S. mutans EMVs also upregulated biofilm formation by early tooth colonizers including Streptococcus mitis, Streptococcus oralis, Streptococcus sanguinis, Streptococcus gordonii, Actinomyces naeslundii, and Actinomyces oris, while biofilm formation by other microbial species including Candida albicans, S. salivarius, S. aureus, Streptococcus anginosus, Streptococcus intermedius, and S. pyogenes were not affected (Senpuku et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also prevalent in S. mutans EMVs were glucosyl hydrolases, Gtfs, and Gbps, all of which are well established S. mutans virulence attributors that play a significant role in facilitating biofilm formation (Lemos et al, 2019). GTFs were recently reported to be carried by S. mutans EMVs, and impaired biofilm formation by a gtfBC mutant was restored by exogenous addition of EMVs harvested from broth culture supernatant of the parent strain (Senpuku et al, 2019). Addition of S. mutans EMVs also upregulated biofilm formation by early tooth colonizers including Streptococcus mitis, Streptococcus oralis, Streptococcus sanguinis, Streptococcus gordonii, Actinomyces naeslundii, and Actinomyces oris, while biofilm formation by other microbial species including Candida albicans, S. salivarius, S. aureus, Streptococcus anginosus, Streptococcus intermedius, and S. pyogenes were not affected (Senpuku et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…GTFs were recently reported to be carried by S. mutans EMVs, and impaired biofilm formation by a gtfBC mutant was restored by exogenous addition of EMVs harvested from broth culture supernatant of the parent strain (Senpuku et al, 2019). Addition of S. mutans EMVs also upregulated biofilm formation by early tooth colonizers including Streptococcus mitis, Streptococcus oralis, Streptococcus sanguinis, Streptococcus gordonii, Actinomyces naeslundii, and Actinomyces oris, while biofilm formation by other microbial species including Candida albicans, S. salivarius, S. aureus, Streptococcus anginosus, Streptococcus intermedius, and S. pyogenes were not affected (Senpuku et al, 2019). Hence, S. mutans EMVs appear to support biofilm formation not only by S. mutans itself, but also by others that may reside in close proximity in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the exogenous addition of EVs from Streptococcus mutans to non-biofilm-forming mutants increases oral biofilm formation. 73…”
Section: Infection and Biofilmmentioning
confidence: 99%
“…For Gram-negative bacteria, vesiculation would allow dna translocation across at least the OM, and potentially the IM and the physical barrier of PG. It has been found that the dna associated with biofilm formation is not simply random genomic dna, but complex, short fragments, 73 which could be specifically associated with EVs.…”
Section: Strainmentioning
confidence: 99%